Essential characteristics of socialist communes and wards in Vietnam today - VŨ THẾ TÙNG (Political Theory Journal, 2026)
Building socialist communes and wards in Vietnam today is a matter of urgent theoretical and practical significance, posed in the nation’s new era of development. The identification of essential characteristics plays an especially crucial role, serving as a basis for localities to construct criteria, models, and organizational methods appropriate to specific conditions. Based on the foundation of Marxism-Leninism, Ho Chi Minh Thought, and the viewpoints of the Communist Party of Vietnam on socialism and the path toward socialism, while concurrently originating from the organizational and operational realities of communes and wards under current conditions, the article initially analyzes the essential characteristics of the model of socialist communes and wards that Vietnam aims for.